EXAMINATION IN THEORY OF ACCOUNTS. - Zlatkovich, Charles T. (The Accounting Review, 1959)
Abstract The theory of Accounts section of the November, 1958, Uniform Certified Public Accountant Examination was given on Friday, November 7, 1958, from 1:30 to 5 :00 P.M. There were two groups of questions; all five questions in the first group were required; two were to be selected from the three in the second group. To save candidates the time of computing their own time budgets for each question, notations of estimated time requirements were furnished for each question to be answered separately and in the aggregate by all questions to be answered out of a group where options are involved. The estimated time allowances were approximately proportional to their point value, the total of which for this examination is 100 points. Each numbered transaction was to be considered completely independent of the others and its related answer should be based on the effect(s) of that transaction alone.